2022
DOI: 10.3390/cells11040709
|View full text |Cite
|
Sign up to set email alerts
|

Human Amnion-Derived Mesenchymal Stromal/Stem Cells Pre-Conditioning Inhibits Inflammation and Apoptosis of Immune and Parenchymal Cells in an In Vitro Model of Liver Ischemia/Reperfusion

Abstract: Ischemia/reperfusion injury (IRI) represents one of the leading causes of primary non-function acute liver transplantation failure. IRI, generated by an interruption of organ blood flow and the subsequent restoration upon transplant, i.e., reperfusion, generates the activation of an inflammatory cascade from the resident Kupffer cells, leading first to neutrophils recruitment and second to apoptosis of the parenchyma. Recently, human mesenchymal stromal/stem cells (hMSCs) and derivatives have been implemented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…The MSC secretome, containing biological factors that include EVs enriched in proteins and miRNAs, has been shown to be strongly involved in the modulation of the IRI phenotype for several reasons. First, it contains immunomodulatory factors, as well as pro-angiogenic and tissue repair properties, which by themselves seem to account for the majority of the therapeutic effects [ 20 , 22 , 252 , 253 , 254 ]. Second, because of the MSC secretome requirement for resolution of IRI, its use has recently been proposed instead of MSC transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The MSC secretome, containing biological factors that include EVs enriched in proteins and miRNAs, has been shown to be strongly involved in the modulation of the IRI phenotype for several reasons. First, it contains immunomodulatory factors, as well as pro-angiogenic and tissue repair properties, which by themselves seem to account for the majority of the therapeutic effects [ 20 , 22 , 252 , 253 , 254 ]. Second, because of the MSC secretome requirement for resolution of IRI, its use has recently been proposed instead of MSC transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Scientific evidence has revealed that both cellular and acellular therapies based on the use of mesenchymal stem/stromal cells (MSCs), represent promising approaches to mitigate IRI-related pathological processes [ 19 , 20 , 21 , 22 ]. MSCs have been found in different tissues, including umbilical cord (UC-MSCs) [ 23 ], bone marrow (BM-MSCs) [ 24 ], adipose tissue (Ad-MSCs) [ 25 ], and placenta (AM-MSCs) [ 26 ], where they participate in the maintenance of stem cell niches and tissue homeostasis [ 27 , 28 ].…”
Section: Mesenchymal Stem/stromal Cell (Msc)-based Therapy As a New S...mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the hUCMSCs could better protect the organ structures and functions at early stage post severe burn. And other preclinical studies also have shown hMSCs therapeutic value in studies of myocardial infarction, diabetes, sepsis, hepatic failure, acute renal failure, and acute lung injury (ALI) [35][36][37][38][39]. But administered hUCMSCs do not massively integrate into the injured tissues, so we speculated reasonably the main mechanism by which hUCMSCs play a role in repairing damaged tissues by paracrine protective cytokines.…”
Section: Shammentioning
confidence: 92%
“…IFN-γ pre-treatment and 3D culture of MSC showed increased production of both growth and immunoregulatory factors. Furthermore, these modified MSCs strongly reduced M1-induced inflammation [ 145 ]. Pre-activation of in vitro cultured MSCs with patient serum allows MSCs to have specific host-related functions and properties, thus allowing for individualized management strategies.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%